Pengaruh Persepsi Sarana dan Prasarana Terhadap Mutu Pelayanan di Rumah Sakit Siaga Al-Munawwarah Samarinda - Claudia, Maria Cindi; Johan, Herni; Nurhasanah, Nurhasanah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Service Quality is a key to improving patient statisfaction in hospitals. Adequate facilities and infrastructure not only support hospital operations but also directly influence patients’ perceptions of service quality. This study aims to analyze the effect of perceptions of facilities and infrastructure on service quality at Siaga Al-Munawwarah Hospital in Samarinda. The study employed a quantitative approach with a cross-sectional design. The study population involved 57.923 outpatients, with a sample of 270 respondents selected through simple random sampling. Data collection was conducted through structured interviews using a questionnaire. Data were analyzed univariately and bivariately using the Wilcoxon test to assess the relationship between variables. Based on analysis, the respondents’ characteristics were as follow: the gender of respondent was predominantly female, totaling 167 individuals (62%); the age group was mostly 31-50 years, with 128 individuals (47%); the most common occupation was housewife, totaling 155 individuals (43%); and the majority of the questionnaires were filled out by the patients themselves, amounting to 165 individuals (61%). The distribution of respondents’ perceptions of facilities and infrastructure showed that 20% fell into the low category, 65% into the medium category, and only 15% into the high category. Meanwhile, the distribution of service quality responses revealed that the highest percentage was in the low category qt 66%, followed by 15% in the high category. The results of this study indicate a p-value of 0.01 (less than 0.05), thus the null hypothesis (Ho) is rejected. The conclusion of this study is that there is a significant relationship between perceptions of facilities and infrastructure and service quality at Siaga Al-Munawwarah Hospital in Samarinda.